Contribution of membrane fouling during Ultrafiltration of Hylocereus Polyrhizus Peel Extract - Azimah, Saman; Mimi Sakinah, A. M.; Zularisam, A. W. (Universiti Malaysia Pahang, 2016)
Betacyanin pigment is red purple colour that can be produced from the peels of Hylocereus polyrhizus fruit. The separation of betacyanin from fruit peels with high pulp content is very tedious due to the high concentration of fouling substances in the fruit peel that is also concentrated in the retentate during processing. The suspended solids usually responsible for this fouling are polysaccharides that come from cellular walls in the fruits, such as insoluble pectins, cellulose, hemicelluloses, and lignin. The high concentration of these macromolecules on the surface of the membrane produces a dynamic layer that, in some cases, forms an impermeable gel-like layer. In this study, ultrafiltration membrane was used as a tool to separate betacyanin pigment from Hylocereus Polyrhizus peel extract. Separation of betacyanin from Hylocereus polyrhizus peel extract was assessed by employing an ultrafiltration membrane reactor system. The effect of transmembrane pressure and crossflow velocity were studied. The fouling membrane can effectively control by changing the crossflow velocity and transmembrane pressure.